Ảnh hưởng của các dạng thù hình tinh thể TiO2 đến sự thay đổi cấu trúc của polyme blend EVA/PLA trong quá trình thử nghiệm gia tốc thời tiết - Công, Đỗ Văn; Hoang, Thái (Vietnam Journal of Chemistry, 2016)
Photo-degradation of poly(ethylene-co-vinyl acetate) (EVA)/poly(lactic acid) (PLA) blend and EVA/PLA/TiO2 nanocomposites was carried out under accelerated weathering stimulation by alternating cycles of UV light and moisture at controlled and elevated temperatures. The degradation of these materials was characterized by Fourier Transform Infrared Spectroscopy (FTIR), color changes, viscosity, tensile test, thermogravimetric analysis (TGA) and Field Emission Scanning Electron Microscopy (FESEM) observation. The increase in the content of oxygen containing groups, color changes; the decrease in viscosity, tensile properties, and thermal stability is the evidences for the degradation of the blend and nanocomposites. After the aging, the appearance of many micro-holes and micro-pores on the surface of the collected samples was observed. The degradation degree of the nanocomposites depended on the TiO2-crystal form. Rutile TiO2 nanoparticles nearly do not effect on the photo-degradation of nanocomposites, while anatase and mixed crystals TiO2 nanoparticles promoted the photo-degradation of nanocomposites, in which, mixed crystals TiO2 nanoparticles showed the highest photo-catalytic activity. Keywords. Poly(ethylene-co-vinyl acetate), poly(lactic acid), titanium dioxide, nanocomposites, photo-degradation, accelerated weathering.